ARTICULATION OF SELAWAT CONCERT FANDOM IN THE CONTESTATION OF POPULAR CULTURE ARENA - Rohmanda, Miranti; Budiman, Manneke (Metahumaniora, 2025)
This article examines the articulation of the selawat concert fan community built in the digital space, specifically Instagram. Selawat concerts are a phenomenon that positions hadroh groups as performers similar to pop music concerts. The arena of selawat concerts became popular after the emergence of participatory fan culture. In this context, cultural theorist Stuart Hall explains that communities will form articulations to create new meanings from a scattering of various elements that can be used to strengthen their cultural identity. This paper explores the multi-layered and interdisciplinary approach of Hall's interpretation of identity and applies it to discuss the identity formation and strategies of selawat fan communities, specifically Syekher Mania, Zahir Mania, and Syubban Lovers. This study analyzes content on Instagram related to Syekher Mania, Zahir Mania, and Syubban Lovers and literature review.